Absence of sex differences in serotonergic control of orbitofrontal cortex neuronal activity - Kailin M. Mooney; Alexander F. Hoffman; Carl R. Lupica (Scientific Reports)
Abstract The orbitofrontal cortex (OFC) is a brain region involved in cognitive processing, especially in tasks that require flexibility in decision-making. Serotonin (5-HT) plays a critical role in mediating OFC-dependent behavior, primarily through its actions at both 5-HT1 and 5-HT2 receptors. Through these receptors, 5-HT acts both pre- and postsynaptically at pyramidal (PyN) neurons and parvalbumin-containing interneurons (OFCPV) to regulate their activity. In a previous study, we reported that the non-selective 5-HT2 antagonist ketanserin inhibited 5-HT-induced membrane currents in OFCPV neurons from female and not male rats, suggesting the possibility that this results from sex-dependent differential 5-HT2A and 5-HT2C receptor expression. Here, we test this hypothesis using subtype-selective antagonists, and we find that 5-HT-mediated depolarization of OFCPV neurons occurs via activation of 5-HT2A, and not 5-HT2C receptors. Additionally, 5-HT2A receptor antagonism was equally effective in OFCPV neurons from males and females, as was the 5-HT2 agonist 2,5-Dimethoxy-4-iodoamphetamine (DOI). These pharmacological data suggest that the sex-dependent effects of ketanserin do not result from differential expression of 5-HT2 receptor subtypes in OFCPV neurons. In addition, 5-HT effects on OFC PyNs are similar in males and females. In light of recent reports of sex-dependent differences in prefrontal cortical function, our results are presented to inform and clarify actions of 5-HT on OFC circuitry.